A Case of Stage I Vulvar Squamous Cell Carcinoma with Early Relapse and Rapid Disease Progression - Marta Peri; Antonino Grassadonia; Laura Iezzi; Patrizia Vici; Michele De Tursi; Clara Natoli; Nicola Tinari; Marinella Zilli (Case Reports in Oncological Medicine)
Squamous cell carcinoma (SCC) is the most common subtype of vulvar cancer. Locoregional surgery is often curative when the tumor is diagnosed at an early stage. However, the disease can unexpectedly evolve with a dismal prognosis even after an early diagnosis. We report a case of a woman who experienced a rapid, chemorefractory tumor progression after surgery for stage IB vulvar SCC.